Recent sequencing and phylogenetic analysis of equine herpesviruses 1 and 4 among different equine populations in Egypt - El Zayat, Mohamed; Shemies, Omayma A; Mosad, Samah M; Rahman, Sahar Abd El (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: Equine herpes viruses (EHVs) are considered one of the most important respiratory pathogens in equids, resulting in serious outcomes for equine health worldwide. The objectives of the current research were the detection, molecular characterization, and isolation of EHV-1 and EHV-4 circulating within different equine populations in Egypt, either clinically or in apparently healthy horses. Material and Methods: A total of 120 field samples were collected, and DNA was extracted. Screening and typing of extracted DNA were done by consensus and conventional PCR assays for detection of EHV-1 and EHV-4, followed by sequencing and phylogenetic analysis to confirm the virus identity. Selected positive samples for both EHV-1 and EHV-4 were subjected to Madin Darby bovine kidney (MDBK) cell lines for virus isolation. Results: The obtained results revealed that 58/120 (48%) samples were positive for EHVs. Typing of positive samples showed that EHV-1 was detected in (48/120) 40% of samples and EHV-4 was detected in (15/120) 12% of samples, while dual infection by both EHV-1 and 4 was detected in five samples. Conclusion: The current study revealed new data on the continuous circulation of EHV-1 and EHV-4 within equine populations in Egypt, and individual horses could be infected by multiple EHVs. In addition, latently infected horses are acting as potential reservoirs for frequent virus reactivation. J. Adv. Vet. Anim. Res., 10(4): 639–646, December 2023 http://doi.org/10.5455/javar.2023.j719